40SiO2–40P2O5–20ZrO2 sol-gel infiltrated sSEBS membranes with improved methanol crossover and cell performance for direct methanol fuel cell applications. (14th August 2020) - Santiago, Ó.; Mosa, J.; Escribano, P.G.; Navarro, E.; Chinarro, E.; Aparicio, M.; Leo, T.J.; del Río, C.
Abstract: Membranes commonly used in direct methanol fuel cell (DMFC) are expensive and show a great permeability to methanol which reduces fuel utilization and leads to mixed potential at the cathode. In this work, sulfonated styrene-ethylene-butylene-styrene (sSEBS) modified membranes with zirconia silica phosphate sol-gel phase are developed and studied in order to evaluate their potential use in DMFC applications. The synthesized hybrid membranes and sSEBS are subjected to an exhaustive physicochemical characterization by liquid uptake, ion exchange capacity, atomic force microscopy, X-ray photoelectron spectroscopy and dynamic mechanical and thermogravimetric analyses. Likewise, the potential use of the prepared membranes in DMFC is evaluated by means of electrochemical characterizations in single cell, determining the limiting methanol crossover current densities, proton conductivities and DMFC performances. The hybrid membranes show lower water and methanol uptakes, higher stiffness, water retention capability, upper power density and lower methanol crossover than sSEBS and Nafion 112. Highlights: Zirconia phosphosilicate-sSEBS membranes are prepared by sol-gel infiltration. Incorporation of inorganic phase into hydrophilic domains is confirmed by AFM and DMA. Infiltration induces strong hydrogen bond interactions between Si–OH, P–OH and SO3 H. Methanol crossover decreases over infiltration time and is lower than sSEBS and N112. Best DMFC performance is reported for the hybrid membrane infiltrated for 40 min.